Pengaruh Likuiditas, Pertumbuhan Penjualan, Asset Turnover Dan Usia Perusahaan Terhadap Struktur Modal (Jurnal Paradigma Akuntansi, 2022)
This study aims to determine the extent of the influence of liquidity, sales growth, asset turnover and company age on the capital structure of manufacturing industrial companies listed on the Indonesia Stock Exchange during 2017-2019. The sample was selected by purposive sampling method and the valid data were 87 companies. The data processing technique uses multiple regression analysis assisted by the SPSS (Statistical Product and Service Solution) program for Windows released 22 and Microsoft Excel 2016. The results of this study indicate that liquidity has a significant and negative effect on capital structure. Sales growth has no significant effect on capital structure. Meanwhile, asset turnover and company age have a significant and positive effect on the company's capital structure. The implication of this research is the need to increase the level of liquidity to reduce debt in the capital structure of a company.